Faktor - Faktor yang Berhubungan dengan Dismenore pada Siswi SMK Negeri 10 Medan Tahun 2013 - Frenita Sophia Purba; Sori Muda Sarumpaet; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Abstract Dysmenorrhea is menstrual pain and cramping that usually centered in the lower abdomen that occurs before or during menstruation. The prevalence of dysmenorrhea in Indonesia in 2008 was 64.25%, consisting 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. The results of Novia research  at SMA St. Thomas Medan in 2012 showed 84.4% of adolescents had  dysmenorrhea, with mild pain intensity of 46.7%, 30.0% moderate pain, and severe pain 23.3%. To determine factors associated with dysmenorrhea at SMK Negeri 10 Medan in 2013, conducted research using cross sectional design. Sample was many 171 students were taken by simple random sampling. Univariate data were analyzed descriptively and bivariate data were analyzed using the chi square test with 95% CI. The result of the research shown that proportion prevalence of dysmenorrhea was 81,30%. The highest proportion of the dysmneorrhea of the respondent at the category ages 15 – 17 years old (85,90%), ages of menarche ≤ 12 years old (83,70%), normal menstrual cycles (82.90%), long periods ≥ 7 days (87.20%), family history (87.10%), underweight (88.00%), and less exercise (85.80%). the result of bivariate analysis, Generally there is a significant association between age (p = 0.020), age of menarche (p = 0.031), duration of menstruation (p = 0.046), family history (p = 0.019), nutritional status (p = 0.043), and exercise habits (p = 0.019) and dysmenorrhea. And there was no significant correlation between menstrual cycle and dysmenorrhea. It is expected that students who have dysmenorrhea accompanied fast menarche age, long term periods, irregular menstrual cycles, and family history of dysmenorrhea in order to see a doctor. And always exercise and keep normal body weight. Keywords: Dysmenorrhea, Adolescent, Risk Factors